The Role Of Islamic Religious Education Teachers In Habituation Dzuhur Congregational Prayers Among Students - Andriansyah Kusuma; Muin Abdullah; Yuni Safitri (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Daily congregational prayers are commonly practiced in public madrasahs, yet the mechanisms behind how such routines are nurtured particularly through the agency of Islamic Religious Education teachers remain underexplored. This study investigates how Islamic Religious Education teachers cultivate the habit of performing the Dzuhur prayer in congregation at MTs Negeri 4 Klaten, the challenges encountered in the process, and the strategies employed to sustain student participation. Adopting a qualitative single case study design, the research involved two Islamic Religious Education teachers and six students selected through purposive sampling. Data were obtained via participatory observation, in-depth interviews, and document analysis, and were processed using Miles and Huberman’s interactive model. The findings indicate that the teachers’ contribution extends beyond instructional roles; they function simultaneously as role models, motivators, supervisors, and character builders. Key barriers include inconsistent student discipline, limited spiritual awareness, infrastructural constraints, and peer influence. To address these issues, the teachers implement persuasive educational approaches, exemplary conduct, close monitoring, regular evaluation, and collaborative coordination with fellow educators. Overall, the study affirms that the personal commitment of teachers is pivotal in transforming worship routines into sustainable character-building practices within the school environment.